1991
DOI: 10.1111/j.1365-3180.1991.tb01776.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term stability of distribution of Alopecurus myosuroides Huds. within cereal fields

Abstract: Summary: The incidence of Alopecurus myosuroides seedheads was monitored annually for 10 years in the cereal fields of a 173‐ha arable and dairy farm. A. myosuroides persisted at low population densities, despite the use of herbicides and grass breaks in the rotation. The distribution of the weed was irregular, with none occurring on at least 60% of the positions surveyed in the cereal fields. Spatial distributions were compared between years, and some significant correlations were found from year to year in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 7 publications
3
85
1
Order By: Relevance
“…remained similar over 10 years; the distribution was more stable in fields which were always sown with cereals· compared with fields in which grass and cereals were rotated. Wilson and Brain (1991) suggests that the reason for this stability is that the majority of seeds of blackgrass are shed close to the parent plant before harvest. Gerhards et al (1997) characterised the spatial stability of common sunflower, velvetleaf, green and yellow foxtail and hemp dogbane in eastern Nebraska.…”
Section: Spatial Heterogeneity Of Weedsmentioning
confidence: 99%
See 2 more Smart Citations
“…remained similar over 10 years; the distribution was more stable in fields which were always sown with cereals· compared with fields in which grass and cereals were rotated. Wilson and Brain (1991) suggests that the reason for this stability is that the majority of seeds of blackgrass are shed close to the parent plant before harvest. Gerhards et al (1997) characterised the spatial stability of common sunflower, velvetleaf, green and yellow foxtail and hemp dogbane in eastern Nebraska.…”
Section: Spatial Heterogeneity Of Weedsmentioning
confidence: 99%
“…For example, Wilson and Brain (1991) found that the distribution of patches of blackgrass (Alopecurus myosuroides Huds.) remained similar over 10 years; the distribution was more stable in fields which were always sown with cereals· compared with fields in which grass and cereals were rotated.…”
Section: Spatial Heterogeneity Of Weedsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research has shown that weed aggregation exists (Marshall, 1988;Wilson and Brain, 1991;Thornton et al, 1990;Wiles et al, 1992;Cardina et al, 1995;Mortensen et al, 1993) and that if herbicides were applied in a spatially varying manner based on weed density, a reduction in herbicide usage would occur Johnson et al, 1995). Thus, sitespecific weed management and integrated weed management [based on the principles of integrated pest management (IPM)] have been proposed as practices which use knowledge of weed variability to achieve economic and environmental goals (Lindquist et al, 1998).…”
mentioning
confidence: 99%
“…Weed patches are considerable stable if they are consistent with location and density over time (Wilson and Brain, 1991). It appeared that C. arvensis patches were stable with respect to their location.…”
Section: Site-specific Herbicide Applicationmentioning
confidence: 96%